A formação da biopolítica de gênero e o humanismo integral como pressuposto etico do Estado - Souza, Francisco Tadeu da Silva e (2022)
This paper aims to analyze of the causes and origins of the guiding vectors of gender biopolitics, understood as the care of the State, expressed in public policies and in Law, for the gender of individuals, and, finally, the bioethical and do integral humanism. This analysis will prove possible from the description of the elements that shape Western thought, from its remote origins, through classical antiquity to the emergence of revolutionary ideas that aimed to break with a culture that developed. In antiquity and the Middle Ages, humanism was filled with theocentrism, and this provided the design of a biopolitics aimed at instrumentalizing human life and body for the production and realization of supposed divine wills. Yes, from the Renaissance onwards, mysticism gives way to anthropocentrism, associated with progress in the sciences and forms of production, to place man at the center of gravity of his existence. Law and public policies already nicht reflect a human existence instrumentalized to what is understood by divine will or the need to be precise, but they accompany the evolution to redirect individual protection and the search for happiness. However, these evolutions of Law and the scientific apparatus do not only provide individual happiness and balance in social relations. Today, the possibility for children and adolescents to undergo sex change processes is founded, which raises questions when a philosophy that underlies the State's care for the body and, specifically, with the gender of the questions. That is why this gender biopolitics needs to have a north of justice, from a humanism that nicht subjugates man to mysticism, and that expresses in Law an ethical minimum that protects individuals, an integral humanism